Competition and the Pricing of Dealer Service in the Over-the-Counter Stock Market - Tinic, Seha M.; West, Richard R. (Journal of Financial and Quantitative Analysis, 1972)
Seha M. Tinic, Richard R. West, Competition and the Pricing of Dealer Service in the Over-the-Counter Stock Market, The Journal of Financial and Quantitative Analysis, Vol. 7, No. 3 (Jun., 1972), pp. 1707-1727